PENGARUH PENGGUNAAN MEDIA ANIMASI KOMPUTER DAN MOTIVASI BELAJAR DALAM PEMBELAJARAN REAKSI REDOKS DAN ELEKTROKIMIA TERHADAP PRESTASI BELAJAR MAHASISWA - Freddy Tua Musa Panggabean; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2015)
Abstract This research aim to know how effect of computer animation instructional media and student motivation for student learning outcomes on teaching redox reaction. The quasy experiment methods conduct and achievement test using as instrument. Data was analysed using inferential statistic method. The results and hypothesis test shows: (1) there is a significant influence the use of computer animation media on learning redox reaction and electrochemical to achievement of students, in which chemistry learning achievement of students taught using computer animation media (84.38) is higher compared chemistry learning achievement of students who are taught without using the computer animation media (78.25), (2) there is a significant influence on learning motivation to achievement of students, in which chemistry learning achievement of students who have a high learning motivation (84.59) higher than chemistry learning achievement of students who have a low learning motivation (78.89), and (3) there is no significant influence of the interaction between the use of computer animation media and learning motivation of students to achievement of student.Kata kunci: Media Animasi, Motivasi, Prestasi Belajar, Kimia.